1996
DOI: 10.1136/gut.39.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the failure of endoscopic injection therapy for bleeding gastric ulcer.

Abstract: (Gut 1996; 39: 155-158)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
11

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 24 publications
2
39
1
11
Order By: Relevance
“…Thus, further studies are needed to clarify this point. Several studies found that ulcers located on the high gastric lesser curvatures or posterior duodenal bulb had increased risks for rebleeding, which locations could be related to difficulty of accurate focusing during endoscopic management (9,17,31). In our cases, there was no significant difference of rebleeding risk according to location of ulcer.…”
Section: Original Articlementioning
confidence: 39%
“…Thus, further studies are needed to clarify this point. Several studies found that ulcers located on the high gastric lesser curvatures or posterior duodenal bulb had increased risks for rebleeding, which locations could be related to difficulty of accurate focusing during endoscopic management (9,17,31). In our cases, there was no significant difference of rebleeding risk according to location of ulcer.…”
Section: Original Articlementioning
confidence: 39%
“…Therefore, if recurrence of bleeding can be prevented, the rate of mortality from ulcer bleeding can potentially be reduced (21).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rebleeding per se is a significant prognostic factor with respect to increased mortality [25][26][27][28]. Due to the fact that the natural history of peptic bleeding is complex, this must be taken into account when designing any controlled trials to evaluate therapy to control non-variceal UGI bleeding.…”
Section: Peptic Ulcersmentioning
confidence: 99%
“…Other factors which are prognostic for early recurrent haemorrhage include: patient age over 65 years, an admission haemoglobin !8 g/dl, clinical shock, haematemesis, recurrent bleeding, severe comorbidity or coagulopathies, an inhospital bleed, the need for transfusions of 15 red blood cell units (RBCU) in the first 24 h after admission or the need for emergency surgery [6,23,24]. Prognostic factors indicative of the failure of endoscopic treatment to control bleeding include: ulcer diameter 12 cm and shock on admission [25,26].…”
Section: Peptic Ulcersmentioning
confidence: 99%